MODEL PEMBELAJARAN SEJARAH DENGAN MENGINTEGRASIKAN NILAI DAN KARAKTER RELIGIUS MELALUI TEKNIK KLARIFIKASI NILAI - Muhamad Arif (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2014)
Abstract: This research was conducted in order to find the teaching of history model that is integrated with the character of religious values ​​through values ​​clarification techniques. Given the results of the study are expected in the form of a draft model of learning, the study was conducted using the method of literature study. There are three points of major concern in this research. First, study the history of the learning materials that will be used as the basis for the development of the model at the same goal of learning, namely the material